2022
DOI: 10.3390/s22114159
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Testbed for IoT Wireless Technologies: Abstracting Latency, Error Rate and Stability from the IoT Protocol and Hardware Platform

Abstract: IoT applications rely strongly on the performance of wireless communication networks. There is a wide variety of wireless IoT technologies and choosing one over another depends on the specific use case requirements—be they technical, implementation-related or functional factors. Among the technical factors, latency, error rate and stability are the main parameters that affect communication reliability. In this work, we present the design, development and validation of a Universal Testbed to experimentally meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…We conclude that the transmission time of the alarm needed to reach the emergency service, starting from the detection of the node emergency, is less than 5 s on average. These values coincide with measurements taken in Saavedra’s research on the different characteristic parameters of the communication technologies [ 34 ]. Nevertheless, the transmission time is subject to several factors, such as the situation of the system with respect to the antennas of the proprietary infrastructure or the saturation of the network, but even so it can be concluded that, because of its fast transmission, the response time by the emergency services will be shorter than traditional systems, in which the human factor is involved in communicating the alarm.…”
Section: Resultssupporting
confidence: 87%
“…We conclude that the transmission time of the alarm needed to reach the emergency service, starting from the detection of the node emergency, is less than 5 s on average. These values coincide with measurements taken in Saavedra’s research on the different characteristic parameters of the communication technologies [ 34 ]. Nevertheless, the transmission time is subject to several factors, such as the situation of the system with respect to the antennas of the proprietary infrastructure or the saturation of the network, but even so it can be concluded that, because of its fast transmission, the response time by the emergency services will be shorter than traditional systems, in which the human factor is involved in communicating the alarm.…”
Section: Resultssupporting
confidence: 87%
“…Hence, all sensor nodes within a network can possess an independent and sensible system, delivering resolutions via an onboard microcontroller [ 29 ]. LoRa signifies the entirety of alternate interaction modules that implement settings to machine-to-machine interfaces that are still external from the presence of networks such as 3G/4G [ 7 , 30 ]. A battery-based optimal communication environment has been similarly suggested as an optimal environment.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, a cloud infrastructure can provide storage and surveillance for a large volume of sensor data and can be accessed from anywhere in the world. Existing technologies such as ZigBee [ 7 ], NB-IoT [ 8 ], and Wi-Fi [ 6 ] are not used in the LoRa transceiver system because of data losses, low coverage, and inefficient transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, 12.3 billion physical devices were connected in 2021, a number that could quickly reach 75 billion by 2025. 9,10 These devices include tiny devices (e.g., sensors, actuators) that are pieces of hardware programmed for specific applications (e.g., e-health, smart city) and used to forward data over the networks (e.g., the Internet). However, there are connectivity and resource challenges in adapting IoT-based solutions, for example, limited communication coverage, limited bandwidth, limited battery life and limited processing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of Things (IoT) is a scalable concept that designs the interconnection of devices (e.g., mobile device, medical devices) to the Internet. Worldwide, 12.3 billion physical devices were connected in 2021, a number that could quickly reach 75 billion by 2025 9,10 . These devices include tiny devices (e.g., sensors, actuators) that are pieces of hardware programmed for specific applications (e.g., e‐health, smart city) and used to forward data over the networks (e.g., the Internet).…”
Section: Introductionmentioning
confidence: 99%